NIKAH SIRI DAN PROBLEMATIKANYA DALAM HUKUM ISLAM (Fakultas Hukum Dehasen, 2017)
Marriage recording aims to realize marital order in society. It is an effort regulated by legislation, to protect the dignity and sanctity (mitsaq al-ghalidz) of marriage, and more particularly of women in domestic life. Through the marriage certificate proven by the marriage certificate, each of which the husband and wife shall obtain a copy, in the event of a dispute or quarreling between them, or one irresponsible, the other may make any legal remedy in order to retain or obtain the rights of the individual, respectively. Because by the deed, the husband and wife have authentic proof of their legal deeds. Among Islamic societies there are still two views on the existing legal or regulatory norms, especially marriage rules. Thus, when looking at the reality of Muslims in particular, there are still many cases of unregistered marriages. Thus there is a dichotomy between religious law and state law. The type of this research is library research (library research).Keywords: Nikah siri, Problem, Islamic Law